Visualization of central auditory processes with functional magnetic resonance tomography - Schmid, N; Tschopp, K; Schillinger, C; Bilecen, D; Scheffler, K; Seelig, J (Laryngo- rhino- otologie, 1998)
Central auditory processes can be visualized using functional MRI in a non-invasive manner and at high spatial resolution. Acoustic stimulation leads to an increase of blood flow of activated areas in the plane of the superior temporal gyrus. Radiologically, this may be visualized based on the long T2-relaxation time of oxyhemoglobin. Ten normal-hearing subjects with ages between 28 and 38 years took part in the investigations. They received binaural, monaural right, and monaural left stimulation with pulsed sine tones of 1000 Hz at a pulse rate of 6 Hz and a sound pressure level of 100 dB SPL. Tonotopic organization of the auditory cortex was visualized using stimulation by pulsed sine tones of 500 Hz and 4000 Hz. Following monaural acoustic stimulation, increased activity of the contralateral auditory cortex could be demonstrated in 9 subjects. In one subject, bilateral activity was noted. Concerning the tonotopic organization of the auditory cortex, we could show that the higher frequencies were localized more medially and anteriorly; the lower frequencies were localized more laterally and posteriorly in the superior temporal gyrus. However, considerable overlap was noted. The overlap of the different frequencies could explain the controversial discussion of the tonotopic organization of the auditory cortex. The results of the monaural acoustic stimulation show clearly the predominant signal increase of contralateral areas in the primary auditory cortex. These results confirm the opinion of the current textbooks that the fiber of the auditory pathways mostly cross. Further investigations using functional MRI are necessary for better understanding of physiological and pathophysiological central-auditory processes.